Genomic characterization of multidrug-resistant Escherichia albertii of fish origin—first isolation and insights into a potential food safety threat - Srinivas, Kandhan; Ghatak, Sandeep; Milton, Arockiasamy Arun Prince; Das, Samir; Puro, Kekungu-u; Pyngrope, Daniel Aibor; Angappan, Madesh; Prasad, Mosuri Chendu Bharat; Bhargavi, Dadimi; Kader, Nur Abdul; Lyngdoh, Vanita; Shilla, Heiborkie; et al. (Frontiers in Microbiology, 2025)
IntroductionEscherichia albertii is an emerging food-borne pathogen with zoonotic potential which is often under-reported due to misidentifications.Materials and methodsThe current study identified E. albertii from retail fish sold in market which was confirmed by phenotypic (colorless colonies on Xylose-Rhamnose-Melibiose MacConkey Agar), genotypic (dual target uniplex PCR-based detection) and genomic methods (CheckM analysis). In this paper we report the phenotypic characters of the isolate and genomic features such as resistome, virulome and mobilome followed by in silico O and H antigen based typing and comparative phylogenomics using various tools (RAST, RGI v6.0.0, ABRicate v1.0.1, PathogenFinder v1.1, PlasmidFinder v2.0, BacAnt v3.3.1, Phigaro v2.4.0, MAFFT v7.490, FigTree v1.4.4).Results and discussionMultidrug resistance was identified with reduced susceptibility to gentamicin, azithromycin, ceftazidime and cefotaxime with a Multiple Antibiotic Resistance (MAR) index of 0.33. Clinically important virulence genes such as eae, cdt, east1 formed a part of the virulome and the probability of being pathogenic to humans was found to be 0.883. The genome was found to harbor mobile genetic elements such as plasmids [IncFIA, IncFIB(pB171), IncFII(pSE11)], transposons (Tn3411, Tn6292) and prophages (Siphoviridae, Myoviridae, Podoviridae). Various typing methods such as biotyping, multilocus sequence typing and in silico O and H antigen typing classified the isolate into biotype 3, multi locus sequence type 4596, O-genotype 4 and H-genotype 1. Phylogenomically, the isolate was placed close to isolate from neighboring country of China. Identification of virulent multidrug-resistant E. albertii from new food source such as fishes increases the risk for fish eating population and necessitates the requirement of further elucidation and development of appropriate control strategies.